Investigate the Effect of Yoga and Meditation Using a Brain-Computer Interface Device - Rajalakshmi, A.; Sridhar, S.S. (International Journal of Intelligent Systems and Applications in Engineering, 2023)
Yoga and Meditation practices started in ancient traditions and have become a popular lifestyle practices due to the linked benefits in improving mental and emotional well-being. Yoga is a physical activity and Meditation is a non-physical activity that involves maintaining a sustained state of physical fitness and mental relaxation. The scientific community is working hard to examine and quantify the impact of these practises, particularly on the brain. EEG data processing allows for a better understanding of the brain’s intricate inner operations. Yoga and meditation EEG may allow access to mental states other than normal awareness. The goal of this study is to get fresh insights into the nature of EEG signals of both yoga and meditations. The captured signals are pre-processed and classified into five sub bands delta, theta, alpha, beta and gamma. For each sub band, statistical features such as mean and standard deviation were extracted. Furthermore, band power for all sub bands also removed. Finally approximate entropy and sample entropy features were extracted. All these features of yoga and meditation categories were analysed and compared.